Estudo do L-histidinato de níquel (II) monohidratado sob condições extremas de temperatura e pressão por Espectroscopia Raman - Maia, José Robson (2014)
In this work bis(L-histidinato)nikel(II) Monohydrate crystals were obtained by slow evaporation method using 1 mol of NiCl2.6H2O, 2 mols of L-histidine and NaOH. Reitveld refinement of X-ray data confirmed the structure. Raman modes obtained at ambient conditions of pressure and temperature were assigned by comparison with results on similar materials and by density functional theory DFT calculations. PED (potential energy distribution) is also present. Raman spectroscopy measurements were performed from room temperature up to 150 oC in the 50- 3500 cm-1 spectral range. For temperatures higher than 125 oC the modes related with the water stretching disappeared as well as the lattice modes disappeared indicating a phase transition undergone by the crystal. DSC experiments support this assumption. By decreasing temperature up to 18 K in the 40-3500 cm-1 spectral range it was observed modifications only in internal modes, so we believe that some conformational change has been occurred in the molecules of bis(L-histidinate)nikel(II) Monohydrate. High pressure experiments were performed from ambient pressure up to 9,5 GPa in the 50-3500 cm-1 spectral range. Disappearance of modes between 0,4 and 0,8 GPa was interpreted as evidences of a structural phase transition undergone by the crystal. A second set of modifications in the spectra indicates other phase transition experienced by the crystal between 2,6 and 3,2 GPa. The spectrum obtained the realizing pressure points out to the irreverbility of the phase transitions.